A clinical guide to sleep disorders in children and adolescents - Stores, Gregory (Cambridge University Press, 2001)
Sleep disturbance is commonplace and causes much personal distress to sufferers and their families. It is implicated in a variety of problems, from poor educational performance or disturbed behaviour to accidents or physical dysfunction. Traditionally, research into sleep disorders has generally been undertaken within separate, unconnected medical disciplines and has mainly involved adults. As sleep disturbance is closely associated with serious problems, identifying and treating sleep disorders early is essential for good long-term health and well-being. Yet there is no up-to-date, comprehensive, one-stop source of information for clinicians concerning sleep disorders in young people. Gregory Stores addresses this need with a cross-disciplinary account of available clinical information and treatments, illustrated by actual cases of sleep problems in the young. This book will be essential reading for all professionals involved in child healthcare from infancy to adolescence, and will also be invaluable to general readers looking for up-to-the-minute information and references.